Single‐Solvent, Ligand‐Free, Gram‐Scale Synthesis of Cs4PbBr6 Perovskite Solids with Robust Green Photoluminescence. Issue 2 (20th December 2019) - Wei, Yunwei; Sun, Ruijia; Li, Yuehua; Zhang, Yuhai; Lu, Yizhong; Li, Xiaoming; Chen, Guozhu; Cao, Bingqiang; Li, Cuncheng; Zeng, Haibo
Abstract: The preparation of luminescent Cs4 PbBr6 perovskite solids with current methods either needs a complex procedure, or needs a variety of ligands, and a combination of good solvents and anti‐solvents. The potential environmental risks are inevitable when they are produced in large scale. Herein, an environmentally friendly route for the mass production of luminescent Cs4 PbBr6 perovskite solids using a single solvent under ambient conditions is presented. Gram‐scale Cs4 PbBr6 perovskite solids are produced within tens of minutes using a small amount of DMF, specifically, 4 mL DMF solution can produce over 10 g products per batch. Because no ligands and anti‐solvents are utilized in the whole procedures, the ligand‐free Cs4 PbBr6 perovskite solids are facilely harvested after the evaporation of solvent. More importantly, the solvent vapor can be recovered and reutilized, which can eliminate the environmental pollution caused by organic solvent. The experimental results revealed that the solvent, reaction time, and PbBr2 /CsBr molar ratios are crucial for the formation of Cs4 PbBr6 perovskite solids and their luminescent performances. Such Cs4 PbBr6 perovskite solids exhibit strong green PL emission, high PL quantum yield and reversible fluorescent response towards heat and light, which enable them to be suitable for applications in optoelectronic devices. Abstract : A pile of perovskites : A ligand‐free and environmentally friendly approach for gram‐scale synthesis of luminescent Cs4 PbBr6 perovskite solids with DMF as solvent under ambient conditions are successful developed. Over 10 g Cs4 PbBr6 perovskite solids with robust green photoluminescence can be produced by using only a few milliliters of DMF solution within tens of minutes, which is suitable for significant applications in optoelectronic devices.